M/EEG Dynamics Underlying Reserve, Resilience, and Maintenance in Aging: A Review - Jauny, Gwendolyn; Eustache, Francis; Hinault, Thomas Thierry (Frontiers in Psychology, 2022)
Cognitive reserve and resilience refer to the set of processes allowing the preservation of cognitive performance in the presence of structural and functional brain changes. Investigations of these concepts have provided unique insights on the heterogeneity of cognitive and brain changes associated with aging. Previous work mainly relied on methods benefiting from a high spatial precision but a low temporal resolution, and thus the temporal brain dynamics underlying these concepts remain poorly known. Moreover, while spontaneous fluctuations of neural activity have long been considered as noise, recent work highlights its critical contribution to brain functions. Here, we synthesize the current state of knowledge from MEG (magnetoencephalography) and EEG (electroencephalography) studies that investigated the contribution of maintenance of neural synchrony and variability of brain dynamics to cognitive changes associated with healthy aging, and the progression of neurodegenerative disease such as Alzheimer disease. The reviewed findings highlight that compensatory phenomena can take place through increased synchrony of higher (>10Hz) frequency bands. Maintenance of young-like synchrony patterns, in particular for both higher and low frequency bands, was also observed in healthy older individuals. Both maintenance and compensatory adjustments appear to be highly related with preserved brain reserve, structural integrity notably. However, increased synchrony was also found to be deleterious in some case, particularly in the case of pathological aging. These results provide major elements on the influence of stability or variability of functional networks as well as maintenance of neural synchrony over time on individual cognitive changes with aging. These findings could provide new and interesting considerations about cognitive reserve, maintenance, and resilience of brain functions and cognition.